CRIF1 gene therapy ameliorates inflammatory bowel disease by suppressing TH17 cells and fibrosis through mitochondrial function regulation - Park, Jin-Sil; Kang, Hye Yeon; Jeong, Ha Yeon; Yang, SeungCheon; Choi, JeongWon; Cho, Sang Hee; Kim, Sol; Lee, Bo-In; Cho, Mi-La (Frontiers in Immunology, 2025)
BackgroundCR6-interacting factor 1 (CRIF1) is a nuclear transcriptional regulator and a mitochondrial inner membrane protein. Although serious modifications of the tissue architecture of the small intestine have been reported in CRIF1-deficient mice, how this may affect the development of inflammatory bowel disease (IBD) remains unclear. We investigated the effects of CRIF1 on mice with colitis.MethodsIn DSS-induced colitis mice administered p3XFLAG-CMV-10-CRIF1, clinical symptoms were evaluated. Mitochondrial morphology in the intestinal tissues of colitis mice and UC patients was observed by electron microscopy. Level of CRIF1 in the splenic mitochondria of colitis mice or human PBMCs were investigated by western blot or real-time PCR, and the amount of IL-17 in the supernatant of healthy PBMCs co-cultured with CRIF1-overexpressing mitochondria was investigated by ELISA.ResultsOverexpression of CRIF1 attenuated the severity of colitis, alleviated weight loss, and intestinal shortening. Moreover, overexpression of CRIF1 significantly reduced the levels of proinflammatory and necroptosis-related factors in colon and inhibited intestinal fibrosis. The intestines of these mice showed a reduced level of CRIF1 and altered mitochondrial morphology. Transplantation of CRIF1-overexpressed mitochondria into mice with colitis alleviated disease severity. Patients with ulcerative colitis exhibited decreased CRIF1 levels with dysfunctional mitochondria in inflamed colonic tissue. CRIF1-overexpressing mitochondria inhibited IL-17 production in PBMCs from healthy control.ConclusionOur findings demonstrate that CRIF1 alleviates IBD by suppressing inflammation and fibrosis by improving mitochondrial function. Improving mitochondrial function through CRIF1 may be a potential therapeutic strategy for IBD.